Design of an elliptical arc-shaped antenna at 37 GHz and performance analysis for 5G on-body application - Gupta, Anupma; Bansal, Shonak; Al Gburi, Ahmed Jamal Abdullah; Forsyth, David I.; Ismail, Mohd Muzafar (Wydawnictwo SIGMA-NOT, 2024)
This paper presents a compact 5G wideband antenna designed for body-centric networks (BCN) operating on the Ka band. The antenna design includes a simple arc-shaped radiator patch with full ground plane and transformer impedance feedline. Computer Simulation Technology (CST) Microwave Studio Suite, a reliable electromagnetic simulation program, is used for the antenna's design and simulation. The antenna was simulated in free-space, and its resonant frequency is found to be 37 GHz, falling within the Ka band and 5G's n260. The proposed antenna has a size of 37.4 mm3, and it offers a wide impedance bandwidth of over 5.7 GHz (34.3-40 GHz). At the resonant point, the antenna exhibits a gain of 4.48 dBi and unidirectional radiation pattern. Parametric studies demonstrated that by reducing the arc width, the antenna bandwidth can be improved but with destroying impedance matching. The antenna is proposed for use in body area network applications. To evaluate its on-body performance, a muscle equivalent body model is virtually developed. The on-body performance is assessed by placing the antenna in close proximity to body model. The results of the on-body simulations showed that at 37 GHz, the reflection coefficient is 29.5 dB ensuring good impedance matching. The simulated on-body gain is found to be 7.05 dBi. A distance based investigation is conducted to study the impact of the human body's presence on the antenna's behavior. The antenna was positioned at four different distances from the human model to compare the results and assess the effects of distance. The on-body simulations showed consistent results with slight deviations, even when the distance from the human body was varied.